2021
DOI: 10.5194/angeo-39-289-2021
|View full text |Cite
|
Sign up to set email alerts
|

Magnetosheath jet evolution as a function of lifetime: global hybrid-Vlasov simulations compared to MMS observations

Abstract: Abstract. Magnetosheath jets are regions of high dynamic pressure, which can traverse from the bow shock towards the magnetopause. Recent modelling efforts, limited to a single jet and a single set of upstream conditions, have provided the first estimations about how the jet parameters behave as a function of position within the magnetosheath. Here we expand the earlier results by doing the first statistical investigation of the jet dimensions and parameters as a function of their lifetime within the magnetosh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…(2020) and Palmroth et al. (2021) have recently reported significantly smaller characteristic sizes for magnetosheath jets using THEMIS and Magnetospheric Multiscale (MMS) data, respectively. The typical jet scales have been estimated to be below ∼0.2 R E , approximately one order of magnitude smaller than previously reported.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(2020) and Palmroth et al. (2021) have recently reported significantly smaller characteristic sizes for magnetosheath jets using THEMIS and Magnetospheric Multiscale (MMS) data, respectively. The typical jet scales have been estimated to be below ∼0.2 R E , approximately one order of magnitude smaller than previously reported.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, 2D global hybrid-Vlasov simulations of magnetosheath jets have been performed with the Vlasiator code using magnetic dipoles with unscaled strengths and mesh resolutions of the order of the proton inertial length (Palmroth et al, 2018(Palmroth et al, , 2021. These simulations generated many small-size jets but none as large as found in the hybrid-PIC simulations.…”
Section: Comparison With 2d Simulationsmentioning
confidence: 99%
“…Nor have we considered the complicated morphology of the jets as they traverse the magnetosheath. Palmroth et al (2021) recently performed a study where they via simulations investigated the evolution of jets. Goncharov et al (2020) also investigated this evolution.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The duration can be used as a measure of the parallel length of the jet, l p , assuming that the jet propagates at the observed ion velocity and that MMS probes close to the center of the jet (Goncharov et al, 2020). However, a recent study by Palmroth et al (2021) indicates that estimating a jet's length scale from spacecraft observations can be misleading. For example, they found that the jets tend to get shorter as they progress through the magnetosheath.…”
Section: Of 14mentioning
confidence: 99%
See 1 more Smart Citation